Perbandingan Retrofit Seismik Struktur Baja Eksisting dengan X-Bracing Dan Inverted V-Bracing - Kamal, Muhammad Iqbal Habibi; Wanto, Sri; Hidayah, Nurul Firkhati (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2024)
Indonesia is a country that is at the meeting point of three of the Earth's main plates, namely the Indo-Australian Plate, the Eurasian Plate and the Pacific Plate, which are currently actively moving. The plate that really influences the situation around the Java region is the pushing of the Indo-Australian plate towards the Eurasian plate. This situation causes the formation of many volcanoes in Sumatra, Java, Bali and Papua, and active movements between plates often cause earthquakes in these regions. Indonesia's geographic location has a high risk of earthquake impacts, but the rapid development and growth of infrastructure can affect the service life of a building structure. Earthquakes are unpredictable dynamic loads, especially for buildings designed according to old design codes and standards, which are vulnerable to earthquake loads. To achieve satisfactory global seismic behavior, it is necessary to evaluate the existing structure and add appropriate reinforcement. This paper analyzes the strengthening of steel structures using X-Bracing and Inverted V- Bracing BRB with the Pushover Analysis Method. The results of this research are presented in the form of a fragility curve which describes the probability of damage before and after strengthening the X-Bracing and Inverted V- Bracing BRB. By knowing the overall structure in the form of a capacity curve, it is possible to rationally evaluate retrofitting strategies.